Arab values before Islam in the collection of Al-ẖnsāʾ a comparative study with the texts of the Holy Qur’an and the Sunnah of the Prophet - Al-Shraiyfeen, Rauf Abdullah; Shraideh, Khaled Sulaiman; Al-Jabali, Khaled Hasan (Dirasat: Human and Social Sciences, 2025)
Objectives: Studying poetry is one of the most important studies that is mainly concerned with the details of the Arabs’ life in the Pre -Islamic Era. Therefore, this study aimed at investigating the Arabic values in that era, and comparing those values with the Holy Qur’an and Sunnah scripts by studying and analyzing Al-Khansa’s poems, who was one of the most prominent poets of pre-Islamic Arab history, to find out the most prominent Arabic values at that time because her poems are considered a source of Arabic history before Islam. Methods: The researchers adopted the comparative analytical research method by studying Al-Khansa’a’s poems, explaining their linguistic vocabulary, and identifying the most prominent Arabic pre -Islamic values in those poems. Then, the researchers compared those values to the values included in Holy Qur’an and the Sunnah to demonstrate how those Arabic values are compatible with Islamic sources. Results: The study identified several values in Al-Khansa’s poetry, and, obviously, she was so proud of those values, which included: honoring the guest, good manners, helping the oppressed, taking revenge, sovereignty, generosity and abundance of giving, protecting the neighbor’s rights and chivalry. The researchers also concluded that all those values are consistent with the Islamic vision of human life. Conclusions: The Holy Qur’an and the Sunnah came to emphasize many of the pre-Islamic Arab values, in confirmation of the Prophet’s (PBUH) saying: “I was sent only to perfect good morals”.